Reconceptualizing Rural Entrepreneurship Discourse from a Social Constructionist Perspective: A Case Study from Iran. Issue 1 (2nd January 2017) - Shahraki, Hassan; Movahedi, Reza
Abstract: In this paper, we use a case study from Iran to present a sociological analysis of rural entrepreneurship discourse. Drawing on social constructionism as the main theoretical paradigm, as well as Anthony Giddens' Structuration Theory (ST), we argue that Iran's National Foundation for Entrepreneurship and Cooperatives (NFEC), a governmental national development plan, has hegemonic features at both the structural and project levels. Our main argument is that there is an urgent need to shift from the rural entrepreneurship discourse to a multifunctional agricultural one as an alternative rural development strategy.